The design of omnidirectional terahertz mirror and TM mode filter based on one-dimensional photonic crystal: Potential for THz communication system - A. Aming (2018)
© 2015 SPIE. Numerical results using transfer matrix method (TMM) of omnidirectional photonic band gap (omni-PBG) for both TE and TM polarizations from 0 to 89 for THz responses are presented. Such omni-PBG design is based on one-dimensional photonic crystal (1D-PC) containing thin slices of 10 pairs of high-resistivity silicon and magnesium fluoride (MgF2) as the high and low refractive index components respectively, in the (HL)10 structure. With a quarter-wavelength thickness of layer, the thickness increase of either high or low index layer increases this PBG redshift for TE as well as TM polarizations. Conversely, decreasing the thickness causes the PBG of both TE and TM polarizations to become blueshift. This also gives rise to the spectral shift for the omni-PBG. High reflectivity omni-PBG within a certain wavelength is found in the range of 390-515 μm. This suggests a practical way of controlling the thickness of layer to achieve a suitable omni-PBG. This structural design shows the potential of omnidirectional mirror as a key element in THz communication system. In addition, the proposed structure shows a probable application based on the polarization sensitivity of the structure. At an angle of incidence greater than 60, the TM polarized mode is highly transmitted whereas the transmittance of the TE polarized mode become nearly zero. The TM mode filter is therefore realized.